Biopreservation: bacteriocins and lactic acid bacteria - Chittora, Deepali; Meena, Bhanu Raj; Jain, Tripta; Sharma, Kanika (Journal of Postharvest Technology, 2022)
Bacteriocinogenic lactic acid bacteria are used in biopreservation of food products. Biopreservation is the new and innovative approach to control the food spoilage is growing significance for several industries and consumers. Lactic acid bacteria are used in biopreservation because of their food grade and generally recognized as safe (GRAS) status. So, the LABs can be helpful to control the frequent growth of pathogens and spoiling microorganisms in food and feed products. Reported literature showing that maximum number of LABs has been isolated from fermented food and dairy products. These isolates may have biopreservation ability, probiotic properties, fermentation ability and antimicrobial activity. Antimicrobial activity is due to production of metabolites such as organic acid, antifungal peptide and bacteriocins. The cell free supernatant of LABs can be purified by ammonium sulfate precipitation method to collect the bacteriocins. These bacteriocins may have antimicrobial activity tested against food contaminating microbes. Later on purification and characterization are important step to identify the bacteriocins to conclude the molecular composition and molecular weight. Several purification strategies have been used for purification of bacteriocins from complex cultivation broth such as salting-out, solvent extraction, ultrafiltration, adsorption-desortion, ion-exchange, and size exclusion chromatography. The characterization of bacteriocins has been done by LC-MS, Mass spectroscopy, FTIR, MALDI-TOF and SDS PAGE. These purified bacteriocins can be recognized as safe and good solution to control the microbial food spoilage at commercial level..